2012
DOI: 10.1097/anc.0b013e3182425aab
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Feeding Practices in the NICU

Abstract: : Research is needed to provide a foundation on which to develop effective enteral feeding protocols that are appropriate for the diversity of infants cared for in the NICU. Such research findings will culminate in the development and implementation of enteral feeding protocols in the NICU, which will result in improved nutrition, growth, and development outcomes for premature infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…Feeding guidelines are becoming common in the NICUs to balance the benefits of EN with the risk of NEC in high-risk infant populations. (17, 18) Minimal EN regimens (trophic feeding) are often used in high risk patients, however broad ranges in trophic volumes (5-20 ml/kg/day) make studies of feeding practices difficult to compare to determine the ideal volume and duration of minimal EN. (19) A study of premature infants showed early feeding (within 48 hours of birth) improved feeding tolerance and decreased exposure to PN, without an increase in NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding guidelines are becoming common in the NICUs to balance the benefits of EN with the risk of NEC in high-risk infant populations. (17, 18) Minimal EN regimens (trophic feeding) are often used in high risk patients, however broad ranges in trophic volumes (5-20 ml/kg/day) make studies of feeding practices difficult to compare to determine the ideal volume and duration of minimal EN. (19) A study of premature infants showed early feeding (within 48 hours of birth) improved feeding tolerance and decreased exposure to PN, without an increase in NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, this routine practice is being challenged in neonatal intensive care [ 10 , 17 , 26 ] PICUs [ 33 ] and across critical care generally [ 4 , 9 , 15 , 18 , 30 ]. The incidence of gastrointestinal complication of vomiting was higher in the routine GRV measured group.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted among neonatal nurses in the United States (US) and in Canada documented that PDA pharmacological treatment is perceived as one of the leading contraindications to enteral feeding in preterm infants [63]. However, whether withholding feeding during pharmacological PDA closure could help preventing the occurrence of GI complications in infants with a hs-PDA is still a matter of debate among neonatologists.…”
Section: Association Between Pda Feeding Practices and Gi Outcomesmentioning
confidence: 99%